2011
DOI: 10.1016/s1674-8301(11)60041-9
|View full text |Cite
|
Sign up to set email alerts
|

Competitive metabolism of L -arginine: arginase as a therapeutic target in asthma

Abstract: Exhaled breath nitric oxide (NO) is an accepted asthma biomarker. Lung concentrations of NO and its amino acid precursor, L-arginine, are regulated by the relative expressions of the NO synthase (NOS) and arginase isoforms. Increased expression of arginase I and NOS2 occurs in murine models of allergic asthma and in biopsies of asthmatic airways. Although clinical trials involving the inhibition of NO-producing enzymes have shown mixed results, small molecule arginase inhibitors have shown potential as a thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 111 publications
0
34
1
Order By: Relevance
“…We (1,2,4,19) and others (6,(14)(15)(16)(17)(18) have shown that arginine metabolic pathways, including iNOS and ARG, are increased in the airway epithelium in asthma. To address whether de novo epithelium to support the greater arginine metabolism via iNOS and ARG2, which is consistent with the tracer-measured increase in whole-body de novo arginine synthesis in asthma.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…We (1,2,4,19) and others (6,(14)(15)(16)(17)(18) have shown that arginine metabolic pathways, including iNOS and ARG, are increased in the airway epithelium in asthma. To address whether de novo epithelium to support the greater arginine metabolism via iNOS and ARG2, which is consistent with the tracer-measured increase in whole-body de novo arginine synthesis in asthma.…”
Section: Resultsmentioning
confidence: 78%
“…Although higher-than-normal levels of arginine/NO have been long described in asthma, and F E NO has been standardized for clinical assessment of inflammation in asthma, we (19) and others (6,(14)(15)(16)(17)(18) have found that ARG activity is increased in asthma, but little was known of the consequences of increased ARG activity for asthma pathobiology. This study reveals that the greater mitochondrial arginine metabolism is linked to changes in mitochondrial endotype and a shift toward oxidative bioenergetic pathways.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Arginase was of particular importance for competing with nitric oxide synthesis. Increased arginase activity results in the production of nitric oxide in the bronchioles and potentiates airway reactivity [29]. Research findings have also suggested that in a murine asthma model, arginine treatment not only ameliorated the inflammatory airway response and attenuated the increases in arginase Fig.…”
Section: Discussionmentioning
confidence: 99%